1976
DOI: 10.1038/icb.1976.7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Aldosterone in the Guinea‐pig — Effect of Oestrus Cycle, Pregnancy and Sodium Status

Abstract: Summary. The blood concentrations of aldosterone, corticosterone and cortisol were measured in conscious, non-stressed guinea-pigs using a double isotope dilution derivative assay procedure. Aldosterone levels in the guinea-pig were high when compared with those of other species. The concentration of aldosterone, 37-9, ± 15-9 ng/100 ml {x ± SD), and cortisol, 31-8 ± 10-1 ng/100 ml, found in non-pregnant females on a moderate sodium intake was significantly greater than in males (aldosterone 22-2 ± 2-4 ng/100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…inner mitochondrial membranes in adreno¬ cortical cells) cannot be excluded, our results do not support the idea of an indirect protection against oxygen radical species by vitamin C via the regenera¬ tion of vitamin E. Plasma concentrations of cortisol and aldosterone in our control animals are high compared to other species. This species difference has been reported before (24)(25)(26) and may be explained in part by a low affinity of the glucocorticoid receptor to cortisol. The affinity of the guinea pig mineralocorticoid receptor (type 1) to aldosterone is the same as in the rat and may not explain high aldosterone plasma concentrations in this species (27).…”
Section: Discussionsupporting
confidence: 48%
“…inner mitochondrial membranes in adreno¬ cortical cells) cannot be excluded, our results do not support the idea of an indirect protection against oxygen radical species by vitamin C via the regenera¬ tion of vitamin E. Plasma concentrations of cortisol and aldosterone in our control animals are high compared to other species. This species difference has been reported before (24)(25)(26) and may be explained in part by a low affinity of the glucocorticoid receptor to cortisol. The affinity of the guinea pig mineralocorticoid receptor (type 1) to aldosterone is the same as in the rat and may not explain high aldosterone plasma concentrations in this species (27).…”
Section: Discussionsupporting
confidence: 48%
“…Indeed Diamond et al (1969) have found higher plasma cortisol levels in adult females than in male guinea-pigs and they have described how plasma cortisol levels in adult females reach their highest level just at the time of oestrus and decrease after testosterone treatment. However, Whipp, Wintour, Coghlan & Scoggins (1976) found no variations of plasma cortisol levels during the oestrous cycle.…”
Section: Discussionmentioning
confidence: 79%
“…The MC receptor of the guinea pig, however, shows no difference from that of other species (Myles & Funder 1994). Since free plasma cortisol levels are much higher in the guinea pig than in the human, while plasma aldosterone is in the same range in both species (Whipp et al 1976), it seems reasonable to assume that a highly efficient mechanism exists to exclude cortisol from the MC receptors in the guinea pig. One of these mechanisms could be 11 ß-HSD-II with a high activity in MC target tissues (Keightley & Fuller 1996), as in the human.…”
mentioning
confidence: 99%